Financial Performance and Non-Financial Factors on Bond Ratings with Earnings Management as an Intervening Variable: Kinerja Keuangan dan Faktor Non Keuangan Terhadap Peringkat Obligasi dengan Manajemen Laba Sebagai Variabel Intervening - Wati, Devi Minggar; Prapanca, Detak (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of financial performance and non-financial factors on bond ratings with earnings management as an intervening variable.This study uses quantitative methods with secondary data as a data source. In this study the population data used are all PT. Pefindo listed on the Indonesia Stock Exchange. The observation period was from the 2017-2020 period. In this study, non-probability sampling technique used in this study was purposive sampling. There are 15 companies PT. Pefindo used as a sample in this study. The data analysis technique used in this research is Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this study indicate that financial performance has an effect on bond ratings. Non-financial factors affect bond ratings. Financial performance has an effect on earnings management. Non-financial factors affect earnings management. Earnings management has an effect on bond ratings. Financial performance affects bond ratings through earnings management. Non-financial factors affect bond ratings through earnings management.